Biological Oxidation Reactions. Issue 21 (28th July 2015) - Vashi, Preeti
Abstract: EurJIC, with Guest Editors Ebbe Nordlander and Wesley Browne, offers a collection of high‐quality papers clustered around the theme Biological Oxidation Reactions – Mechanisms and Design of New Catalysts. This cluster issue is based on the COST Action CM1003 with the same name and presents the advances in designing new biological, biomimetic and bioinspired catalysts. Abstract : EurJIC, with Guest Editors Ebbe Nordlander and Wesley Browne, offers a collection of high‐quality papers clustered around the theme Biological Oxidation Reactions – Mechanisms and Design of New Catalysts. This cluster issue is based on the COST Action CM1003 with the same name and presents the advances in designing new biological, biomimetic and bioinspired catalysts.